High Stakes Gambling in the Master Class - Lynn Z. Bloom; Carla Hill (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
High Stakes Gambling in the Master Class explores some of the unarticulated intangibles in a relationship between Master Teacher and Honors Student (who collaborated in writing this essay), calculated to produce a distinguished honors thesis, sometimes out of thin air, gambling, playing the hunches that will allow a gleam in the eye to metamorphose into gold on the page.